Green Credit on Gross Domestic Product in Turkey - Ahmed Muaz Yakup Og'lu (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to evaluate the impact of Green Credit on Gross Domestic Product (GDP) in Turkey. Green Credit refers to a financial tool focused on supporting sustainable and environmentally friendly projects. This research utilizes secondary data collection methods from various reliable sources and then applies statistical analysis, such as regression analysis, to assess the relationship between green credit provision and GDP growth in Turkey. The results concluded that Green Credit has a significant positive influence on Turkey's GDP. The findings provide important insights into the contribution of green credit policies in promoting sustainable economic growth and environmental preservation in Turkey. This study has relevance in planning and implementing economic policies that support sustainable development.